2009
DOI: 10.1143/jjap.48.076004
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Plasma Treatment on Adsorbed Iodine as a Catalyst in Chemical Vapor Deposition of Copper and Application to Filling of Deep Trenches with High Aspect Ratios

Abstract: Plasma treatment was introduced in order to control the catalytic properties of iodine in catalyst-enhanced chemical vapor deposition (CECVD) of copper (Cu). The iodine adatoms are deactivated (i.e., lose their catalytic effect) by forming Cu-I bonds through reaction with Cu atoms by the bombardment of ions during the plasma treatment. The surface concentration of effective iodine adatoms that can act as catalysts decreases exponentially with an increasing of ion exposure which is the product of ion flux and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Interestingly, the authors found that the hfac desorbed from the surface as a dimer. This discovery led to a flurry of research with a variety of precursors, 14,15 surface treatments 16,17 and substrates. 18 Molecular iodine has also been used to catalyze copper metal deposition.…”
Section: Iodine Catalyzed Copper Depositionmentioning
confidence: 99%
“…Interestingly, the authors found that the hfac desorbed from the surface as a dimer. This discovery led to a flurry of research with a variety of precursors, 14,15 surface treatments 16,17 and substrates. 18 Molecular iodine has also been used to catalyze copper metal deposition.…”
Section: Iodine Catalyzed Copper Depositionmentioning
confidence: 99%
“…Interestingly, the authors found that the hfac desorbed from the surface as a dimer. This discovery led to a flurry of research with a variety of precursors, [95,96] surface treatments, [97,98] and substrates. [99] Molecular iodine has also been used to catalyze copper metal deposition.…”
Section: Iodine Catalyzed Copper Depositionmentioning
confidence: 99%